Hubungan Pemakaian Alat Pelindung Telinga (APT) Pada Pekerja Industri Terhadap Resiko Noise Induced Hearing Loss (NIHL) - Annisa Auliya Dien Safitrie; Winda Trijayanthi Utama (Majority, 2021)
Noise Induced Hearing Loss (NIHL) is a form of hearing loss caused by noise caused by a work environment that is exposed for a long time. Noise is sound that is produced with an uncertain intensity and volume. Noise sources or sound sources that exceed 85 dB have an impact on the damage to the inner ear meaning receptors. Workers who work in an environment with a noise source above 85dB and with an exposure time of more than 8 hours a day without any rotation (shift) will greatly impact NIHL permanently for a long period of time if they do not use adequate ear protection equipment (APT). The research that has been carried out by Fitriyani et al in 2016, involved 10 respondents who work in the weaving department of a textile company located in Salatiga. The results obtained from 10 respondents who are workers in the weaving department, 70% of workers do not use ear protection in the form of ear plugs while working, 30% of respondents wear ear protection in the form of ear plugs when working, some workers reported buzzing ears due to noise generated in work environments with noise levels above 99 dB. The high prevalence of hearing loss in workers is due to the low wearing of PPE while working in a noisy work environment. Based on the studies that have been conducted, the low use of ear protection is a factor in the high number of NIHL among workers.